Aproximación a los proyectos de colonias ganaderas alemanas en Chile y sus discursos imperialistas (Llanquihue, 1898-1912) - Muñoz Sougarret, Jorge Ernesto (Jahrbuch für Geschichte Lateinamerikas, 2025)
At the beginning of the 20th century, the diplomatic position of the Chilean government had weakened as a result of international condemnation of its actions after the War of the Pacific. With a view to reversing this process, Chile sought support from European countries, particularly Germany. Bremen business groups saw an opportunity to establish themselves and produce wool for export, forming companies in alliance with prominent Chilean political actors, who pressured the government to obtain public land concessions. This article problematizes the thesis of the German colonialist project in Chile, indicating that he responded to a rhetorical appeal of the German chancellor in Chile and that he had no correlate in Germany’s foreign policy.